Exploring the Prevalence of Clozapine Phenotypic Poor Metabolizers in 4 Asian Samples: They Ranged Between 2% and 13%. Issue 6 (November 2019) - Ruan, Can-Jun; Wang, Chuan-Yue; Tang, Yi-Lang; Lin, Shih-Ku; Lee, Seung-Tae; Hong, Kyung Sue; Rajkumar, Anto P.; Jacob, Kuruthukulangara S.; de Leon, Jose
Abstract: Purpose/Background: Clozapine clearance is influenced by sex, smoking status, ethnicity, coprescription of inducers or inhibitors, obesity, and inflammation. In 126 Beijing inpatients, we measured repeated trough steady-state serum concentrations and identified 4% (5/126) who were phenotypical poor metabolizers (PMs); none were ultrarapid metabolizers (UMs). They were defined as being 2 SDs beyond the means of total clozapine concentration/dose ratios stratified by sex and smoking. Using this definition, this study explores the prevalence of PMs and UMs using data from 4 already published Asian samples. Three samples were East Asian (Beijing 2, Taipei, and Seoul); one was from South India (Vellore). Findings/Results: The prevalence of phenotypical PMs ranged from 2% to 13%, but inflammation was not excluded. The prevalence was 7% (14/191) for Beijing 2, 11% (8/70) for Taipei, 13% (9/67) for Seoul, and 2% (2/101) for the Vellore sample. Five phenotypic PMs appeared to be associated with extreme obesity. Phenotypic UM prevalence ranged from 0% to 1.6% but may be partly explained by lack of adherence. A Vellore phenotypic UM appeared to be associated with induction through high coffee intake. Implications/Conclusions: Approximately 10% of Asians may be clozapine PMs and may need only 50 to 150 mg/d to get therapeutic concentrations. Future studies combining gene sequencing for new alleles with repeated concentrations and careful control of confounders including inhibitors, inflammation, and obesity should provide better estimations of the prevalence of phenotypic clozapine PMs across races. Clozapine UM studies require excluding potent inducers, careful supervision of compliance in inpatient settings, and multiple serum concentrations. Abstract : Supplemental digital content is available in the text.